Cross-border issues in the development of medical tourism in Malaysia: legal challenges and opportunities - Jahn Kassim, Puteri Nemie (Thomson Reuters, 2009)
Strategically located at the crossroads of Asia, Malaysia has become one of the key players in the fast-growing and lucrative market for health care services in Asia. Medical travel across international boundaries has been made possible through affordable airfares and the favourable exchange rates of the Malaysian ringgit has contributed to the rise of the "medical tourism phenomenon" where medical travel is combined with visiting popular tourist destinations in Malaysia. Further, competitive medical fees and modern medical facilities have also made Malaysia a popular destination for medical tourists. Nevertheless, the increased number of foreign patients has opened up possibilities of Malaysian health care providers being subjected to malpractice claims and triggering a myriad of cross-border legal issues. Presently, there is no internationally accepted legal framework to regulate medical tourism and issues of legal redress in relation to unsatisfactory provision of treatment across international boundaries. The economic benefits of medical tourism must be based upon a solid legal regulatory framework and strong ethical standards as well as upon high-quality medical and health care services. It is therefore important to assess the existing legal framework affecting the development of medical tourism in Malaysia in order to explore the gaps, deficiencies and possibilities for legal and regulatory reform.